2012
DOI: 10.1161/circep.112.975029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Adenosine Test at Repeat Atrial Fibrillation Ablation Procedure

Abstract: Correspondence to Shinsuke Miyazaki, MD, Cardiology Division, Cardiovascular Center, Tsuchiura Kyodo Hospital, 11-7 Manabeshin-machi, Tsuchiura, Ibaraki 300-0053, Japan. E-mail mshinsuke@k3.dion.ne.jp Background-Pulmonary vein reconnection after electrical isolation is commonly observed in the context of atrial fibrillation ablation and is associated with recurrent atrial tachyarrhythmias. Adenosine test was been performed to identify acute dormant conduction immediately after pulmonary vein isolation at index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…Although Datino et al elegantly demonstrated that adenosine acutely restores the PV-LA conduction by hyperpolarizing the PV cardiomyocytes and activating the outward K+ currents leading to a cellular hyperpolarization, especially in atrial cells, as well as an increase in the INa+ as a result of removing the voltage-dependent inactivation, not all the DC sites revealed by this electrical action of adenosine could always be precisely predicted in the present study [15]. Miyazaki et al reported five patients in whom DC leading to late recurrent atrial arrhythmias after AF ablation could be revealed by an adenosine test during the repeat ablation procedure, and which also lead to the complete freedom from recurrent atrial arrhythmias [16]. However, they speculated that the evaluation of the genuine contribution of the adenosine test was quite difficult because of the possibility of time-dependent spontaneous PV reconnections and the impact of RF-induced reversible tissue edema or inflammation.…”
Section: Mechanisms Of the Different Response To Adenosinecontrasting
confidence: 51%
“…Although Datino et al elegantly demonstrated that adenosine acutely restores the PV-LA conduction by hyperpolarizing the PV cardiomyocytes and activating the outward K+ currents leading to a cellular hyperpolarization, especially in atrial cells, as well as an increase in the INa+ as a result of removing the voltage-dependent inactivation, not all the DC sites revealed by this electrical action of adenosine could always be precisely predicted in the present study [15]. Miyazaki et al reported five patients in whom DC leading to late recurrent atrial arrhythmias after AF ablation could be revealed by an adenosine test during the repeat ablation procedure, and which also lead to the complete freedom from recurrent atrial arrhythmias [16]. However, they speculated that the evaluation of the genuine contribution of the adenosine test was quite difficult because of the possibility of time-dependent spontaneous PV reconnections and the impact of RF-induced reversible tissue edema or inflammation.…”
Section: Mechanisms Of the Different Response To Adenosinecontrasting
confidence: 51%
“…ATP tests were undertaken with the same protocol as during the index procedure even in cases without any PV reconnections at baseline(14). When an arrhythmogenic SVC was identified during the procedure(Figure 1), an electrical isolation was performed.…”
mentioning
confidence: 99%
“…The mechanism has been related to incomplete lesions, which leaves damaged but viable muscle sleeves that can recover, 11 and adenosine/ATP test has been reported to be a useful to identify the dormancy after PV isolation at acute [12][13][14] and chronic phases. 15 However, the clinical impact of adenosine/ ATP injection on SVC reconnection has not been evaluated. The objective of this study is to investigate the clinical impact of ATP injection on arrhythmogenic SVC in the context of AF ablation.…”
mentioning
confidence: 99%